Torrefaction of food waste as potential biomass energy sources - Mazni, Ismail; Rahsya Nur Udzaifa, Abdul Rahman; Ruwaida, Abdul Rasid; Noor Ida Amalina, Ahamad Nordin (Universiti Malaysia Pahang, 2018)
Torrefaction is a mild form of pyrolysis that takes place at temperature between 200 – 300°C, that aims to improves the properties of the treated biomass, producing high quality solid biofuels with lower moisture content and higher energy density. This thermal pre-treatment is commonly carried out in an inert environment, whereby the treated biomass maybe stored for longer period, and is suitable to be applied for energy production processes such as combustion and gasification. The objective of this study is to investigate the improvement of chemical compositions and energy potential of torrefied FW in a fixed bed reactor. The torrefaction process was carried out in a fixed bed reactor with continuous flow of nitrogen, evaluating the effect of temperature (220°C to 260°C), residence time (15 to 60 minutes) and particle size (500 μm to more than 1 mm).